2009
DOI: 10.1603/022.038.0416
|View full text |Cite
|
Sign up to set email alerts
|

Endophyte-Mediated Resistance to Herbivores Depends on Herbivore Identity in the Wild GrassFestuca subverticillata

Abstract: Understanding factors that affect the context dependency of species interactions has been identified as a critical research area in ecology. The presence of symbionts in host plants can be an important factor influencing the outcome of plant-insect interactions. Similarly, herbivore identity can alter the outcome of plant-symbiont interactions. Symbiotic foliar fungal endophytes confer resistance to herbivores in economically important agronomic grasses, in part through the production of alkaloids. Although en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 69 publications
4
25
0
Order By: Relevance
“…The results herein further document variable effects of E+ grasses on the preference and performance of phytophagous insects (Breen 1994;Clement et al 1994;Saikkonen et al 1999;Afkhami and Rudgers 2009;Clement 2009;Popay 2009) by showing that two graminoid pests responded differently to Neotyphodium infection of wild P. alpinum. In 48 hour preference experiments, R. padi preferred E-over E+ test plants.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The results herein further document variable effects of E+ grasses on the preference and performance of phytophagous insects (Breen 1994;Clement et al 1994;Saikkonen et al 1999;Afkhami and Rudgers 2009;Clement 2009;Popay 2009) by showing that two graminoid pests responded differently to Neotyphodium infection of wild P. alpinum. In 48 hour preference experiments, R. padi preferred E-over E+ test plants.…”
Section: Discussionsupporting
confidence: 72%
“…Since the 1980s, much has been learned about factors that influence the outcome of grass-endophyteinsect interactions. For example, the expression and type of insect resistance (antixenosis, antibiosis) may be affected by host grass species/genotype, endophyte strain (including associated alkaloid profile), and insect species/genotype involved in a given interaction (Breen 1994;Clement et al 1994;Clement et al 2005;Afkhami and Rudgers 2009;Bieri et al 2009;Cheplick and Faeth 2009;Popay 2009;Crawford et al 2010). Today, the number of herbivorous insects that have been reported to be negatively affected by endophyte-infected (E+) grasses has grown to over 40 species (Kuldau and Bacon 2008;Popay 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Note that most of these studies used generalist insect pest species, such as the armyworm and bird oat cherry aphid, in bioassay tests. At the other end of the spectrum, native invertebrate herbivores sometimes prefer and perform better (e.g., Saikkonen et al, 1999,Tibbets and Faeth, 1999and Afkhami and Rudgers, 2009 or reached higher abundances Shochat, 2010 andJani et al, 2010) on infected native grasses, in direct contradiction to the predictions of DMH. Thus, support for the DMH hypothesis appears much more equivocal in native grasses than in agronomic grasses, especially when native insect herbivores are considered.…”
Section: Introductionmentioning
confidence: 80%
“…The outcomes of these studies span the range of negative to neutral to positive effects of endophyte infection. Some studies involving native grasses show reduced herbivory or increased insect deterrence on infected grasses relative to uninfected grasses (Christensen and Latch, 1991, Brem and Leuchtmann, 2001, Gonthier et al, 2008, Clement et al, 1997, Clement et al, 2005, Tintjer and Rudgers, 2006and Afkhami and Rudgers, 2009, whilst other studies showed no difference (Christensen and Latch, 1991, Lopez et al, 1995, Clement et al, 1997, Tintjer and Rudgers, 2006and Afkhami and Rudgers, 2009, depending on herbivore species and endophyte strain. Note that most of these studies used generalist insect pest species, such as the armyworm and bird oat cherry aphid, in bioassay tests.…”
Section: Introductionmentioning
confidence: 99%
“…Breen 1994;Clay et al 1985;Popay and Rowan 1994). However, there are only a few studies that have considered the impact of grass endophytes on arthropod communities or functional groups (e.g., Afkhami and Rudgers 2009;Faeth and Shochat 2010;Jani et al 2010). In this study, we used a whole-invertebrate community survey of a controlled common garden experiment to test how invertebrate diversity and community structure, and the number of individuals in functional invertebrate taxa and guilds differs between (i) endophyte infected (E+), endophyte free (E-), and manipulatively endophyte-free (ME-) tall fescue, (ii) host plants of different origin (wild populations from Åland, Gotland, coastal Sweden and one agronomical cultivar, K-31 from USA), and (iii) host plants growing in different abiotic environments (nutrient and water treatments).…”
Section: Introductionmentioning
confidence: 99%